SISTEM INFORMASI MANAJEMEN RUMAH SAKIT WELASASIH AMBARAWA - Agus Tinus Setiawan; Rika Putri Permadani (LPPM STMIK Pringsewu, 2016)
Writing is called Management Information Systems Houses Saki Welasasih Ambrawa is to discuss the management of patient data at the Hospital Welasasih using iteration method and developed a management information system based desktop using Microsoft Visual Studio 2008 and Microsoft SQL Server 2008 as database and network (LAN) as media for communicating data between computers with each other in doing the planning phase, analysis phase, design phase, the analysis of the system running, interviews and observations as well as the collection of data to obtain the information needed. User needs is described by use case use case diagrams and a glossary. The design method to describe the process of Diagram Context and System Data Flow Diagrams, data modeling to describe the ERD, interface design program as a liaison between users and databases. From the results of the implementation of management information systems Hospital welasasih with the aim to facilitate the hospitals in the delivery of patient information and management can process data quickly, providing the information needed by management and the patient quickly and accurately and can store data securely so that it can help in the process of service to the community.